Strengthening the Implementation of Differentiated Learning in Inclusive Elementary Schools Through the OL (Organizational Learning) Approach - Trimurtini, Trimurtini; Waluya, Budi; Nugraheni, Nursiwi; Bektiningsih, Kurniana; Hendikawati, Putriaji (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The purpose of this community service activity is to improve the knowledge and skills of class teachers in designing differentiated learning programs. The method of implementing community service activities includes 4 stages that adopt the OL (Organizational Learning) approach. The four stages in OL are socialization, externalization, combination, and internalization. The results of the activities have been carried out in the socialization and externalization stages, where teachers have planned diagnostic tests for the basis for making differentiated learning tools. The participants' initial knowledge of differentiated learning scored 50, then increased by 39%, to reach a score of 89. The achievement of the score of increasing knowledge about differentiated learning exceeded the planned indicator of 75. The conclusion of the results of this Community Service activity is that the OL stage is used effectively in optimizing the understanding and practice of differentiated learning in Inclusion Elementary School.